New Product Presale Strategies considering Consumers’ Loss Aversion in the E-Commerce Supply Chain - Chongfeng Lan; Jianfeng Zhu (Discrete Dynamics in Nature and Society)
New product presale is a strategic behavior of manufacturers to transfer inventory risks to consumers. The research purpose of this paper is to examine the presale discount, inventory, and service level decisions in an e-commerce supply chain, where the first period is the presale period and the second is the selling period for the new product. First, consumers were divided into two types—those who are risk averse and those who are not. Then, considering different presale discounts applied for new products, three presale strategy models were discussed: no-presale strategy, presale strategy with a moderate discount, and complete presale strategy, and the optimal decisions of e-commerce supply chain members were obtained under different valuations of the new product by consumers. Finally, the effects of the correlation coefficient between the numbers of the two types of consumers, the loss aversion degree of consumers, and the marginal profit in the sales period on the optimal discounted price and the maximum expected profit were analyzed. The conclusions of this article show that the presale strategy is not always optimal but depends on the parameters of the market and the type of consumers. For example, when the correlation coefficient between the two types of consumers is high, it is more profitable for the suppliers if they choose the presale strategy with a moderate discount, while e-commerce platforms tend to adopt the no-presale strategy. The optimal discounted price in the complete presale case is not necessarily lower than that in the moderately discounted presale case. If the marginal profit is high in the normal sales period or consumers are less averse to losses, suppliers are more likely to adopt the complete presale strategy. The research conclusions provide some theoretical reference for companies in the development of new product presale strategies in the e-commerce supply chain.